Critical Analysis of the Risks in the Use of the Internet and Social Networks in Childhood and Adolescence - Núñez-Gómez, Patricia; Larrañaga, Kepa Paul; Rangel, Celia; Ortega-Mohedano, Félix (Frontiers in Psychology, 2021)
Kids are people who consume content on the Internet very frequently and actively participate in social networks, so it is necessary to know the risks of their use by children and adolescents, in order to propose a critical analysis of them. This work is the result of two research projects: a qualitative analysis to determine attitudes towards the safe use of the Internet; and another quantitative analysis to measure the use of devices and Apps. The main results are that children are aware of the risks to which they are exposed; there are also intergenerational tensions between adults and children in terms of use, the difficulty in achieving consensus and quality accompaniment; and there was a relaxation of parental rules for accessing the Internet due to the lockdown in Spain by COVID-19 where there was an intensive use of devices related to socialization, entertainment, and learning. Children have transcended the physical and digital space considering it as a whole, so they must be given the tools, competences and security to fully develop their digital identity.